ANALISIS ARUS KAS TERHADAP LIKUIDITAS PT. HOTEL MANDARINE REGENCY TBK PERIODE 2008-2012 - Agustina, Dewi (Jurnal Akuntansi AKUNESA, 2013)
Statements of cashflows can provide information to the management about the liquidity of companies. The research aims to determine the cash flow on liquidity of  the registered hospitality company in Indonesian Stock Exchange (IDX), especially PT. Hotel Mandarine Regency Tbk. The research method using descriptive method with cash flows from operating, investing and financing activities and liquidity (current ratio) as the variable. The results of this research showed the company?s cash flow surplus, except in 2009 anda 2011. The liquidity of PT. Hotel Mandarine Regency Tbk was liquid that judged from current ratio. Keywords : cash flows, liquidity, current ratio